Corporate Social Responsibility as a Conflict Between Shareholders - Barnea, Amir; Rubin, Amir (2010)
In recent years, firms have greatly increased the amount of resources allocated to activities classified as Corporate Social Responsibility (CSR). While an increase in CSR expenditure may be consistent with firm value maximization if it is a response to changes in stakeholders’ preferences, we argue that a firm’s insiders (managers and large blockholders) may seek to over- invest in CSR for their private benefit to the extent that doing so improves their reputations as good global citizens and has a “warm-glow” effect. We test this hypothesis by investigating the relation between firms’ CSR ratings and their ownership and capital structures. Employing a unique data set that categorizes the largest 3000 U.S. corporations as either socially responsible (SR) or socially irresponsible (SI), we find that on average, insiders’ ownership and leverage are negatively related to the firm’s social rating, while institutional ownership is uncorrelated with it. Assuming that higher CSR ratings is associated with higher CSR expenditure level, these results support our hypothesis that insiders induce firms to over-invest in CSR when they bear little of the cost of doing so.
Keywords: Corporate Governance; Ownership structure; Corporate Social Responsibility